Nuevas territorialidades Desafíos para América Latina frente al Siglo XXI - LAURELLI, Elsa dir. (AL MARGEN, 2004)
Otro descriptor: MUNDIALIZACION.Otros autores: LINDEMBOIM, Javier; GONZALEZ, Marina; ABRAHAM, Helena; MONTAÑA, Elma; TORRES, Laura; PATIÑO TOVAR, Elsa; BANDIERI, Susana; RUSSO, Cintia; SCHIAVO, Ester; RAPOSO, Isabel; QUIRIGA, Sol; COPPOLECCHIO, Leandro; PANAIA, Marta; LILJESTHROM, Moira; CARRIQUIRIBORDE, Helena; FLORES, Oscar; SCHWEITZER, Alejandro; SCHWEITZER, Mariana; LENCIONI, Sandra; DE JONG, Gerardo; CACERES, Alicia; GARCIA, Alicia; AQUINO PIRES DO RIO, Gisela